Study of medial end of fourth ribs with special reference to changes in pit shapes according to age, a qualitative approach - Doshi, Sunil M.; Mangal, H. M.; Kyada, Hetal; Shah, Jainik; Vijapura, Makbul Ali; Bhuva, Shailesh (International Journal of Research in Medical Sciences, 2017)
Background: The objectives of this study were to find changes of pit shape at sternal end of fourth ribs in accordance with age in males, to find bilateral variability in changes of pit shape according to age and to compare the data with previous study. Methods: Total 180 ribs were obtained from male cadavers brought for post-mortem examination. Out of which 140 ribs belonged to 70 cases were included in the study. Each rib was classified according to different stages of pit shape. The data derived were statistically analysed. Results: Pit shape changes from shallow dent to ‘V’, from ‘V’ to ‘U’, from ‘U’ to ‘wide mouth U’ up to sixties of age and after that the quality of the walls surrounding the pit decreases without changes in shape of pit. There was no any bilateral variation found in pit shape changes for age. Conclusions: Changes of pit shape at sternal end of fourth ribs are age dependent without bilateral variations. Age estimation by this method gives general idea about the age in decades only.